Grit, grace, and gumption; or sand, suavity, and sense - Milner, Paul Chambers (My University, 1891)
Introduction: People have different ideas as to what are the essentials of success in life or even as to what success really is. The reason for this is principally, that they look at the end of life from different standpoints. One person tries to give the essentials for success in the business world, others, for success in social circles, and some, the qualities necessary for religious success. But these are only views of partial success, as a man, to have true success, must succeed in business, society and religion. Notwithstanding the extensive field, a few very expressive and suggestive words will tell the whole story, and it would be hard to find any better words for this purpose than “Grit, Grace and Gumption” or their synonyms, “Sand, Suavity, and Sense.” Let us consider these separately and then see how they are necessarily connected in true success. When we speak of grit, we do not mean the bulldog tenacity which characterizes some men and that makes them little more than brutes. Neither do we mean that peculiar quality called perversity of human nature, or spunk, in a man, and stubborn in a mule, as that comes only in jerks and starts and causes him to hold out against everything no matter how reasonable. What is meant, however, is that strength of will, that silent determination which works slowly but steadily onward toward the end to be accomplished and which can be turned back on its own path of necessity demands.
Citation: Milner, Paul Chambers. Grit, grace, and gumption; or sand, suavity, and sense. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Success; Character; Business; Society; Religion; Theses; Manuscripts (documents)